Community-based hepatitis B screening: what works? - Robotin, Monica C. (Springer India, 2014)
INTRODUCTION: Chronic hepatitis B (CHB) affects over 350 million people worldwide and can lead to life-threatening complications, including liver failure and hepatocellular cancer (HCC). Modern antiviral therapies could stem the rising tide of hepatitis B-related HCC, provided that individuals and populations at risk can be reliably identified through hepatitis B screening and appropriately linked to care. Opportunistic disease screening cannot deliver population-level outcomes, given the large number of undiagnosed people, but they may be achievable through well-organized and targeted community-based screening interventions. MATERIAL AND METHODS: This review summarizes the experience with community-based CHB screening programs published in the English-language literature over the last 30 years. RESULTS: They include experiences from Taiwan, the USA, The Netherlands, New Zealand, and Australia. Despite great variability in program setting and design, successful programs shared common features, including effective community engagement incorporating the target population’s cultural values and the ability to provide low-cost or free access to care, including antiviral treatment. CONCLUSION: While many questions still remain about the best funding mechanisms to ensure program sustainability and what the most effective strategies are to ensure program reach, linkage to care, and access to treatment, the evidence suggests scope for cautious optimism. A number of successful, large-scale initiatives in the USA, Asia–Pacific, and Europe demonstrated the feasibility of community-based interventions in effectively screening large numbers of people with CHB. By providing an effective mechanism for community outreach, scaling up these interventions could deliver population-level outcomes in liver cancer prevention relevant for many countries with a large burden of disease.